ACEHNESE LITERATURE: TRANSLATION VARIATION OF VERSES IN MUNAJAT PUTROE DI BEUTOUNG (MPB) - Nurul Fadhillah; M. Husnan Lubis; Tengku Silvana Sinar; Eddy Setia (Corolla International Conference, 2022)
Munajat Pocut di Beutong (MPB) is manuscript in the form of Verses written in Jawi in Acehnese (SL), and translated into Indonesian (TL). The text was rewritten in a book and published in 2012. There are many verses repeated in the text, but some of the translations given were the same and some were different, this what researcher called as translation variation. The variation occurred is due to certain strategies applied by translators. This study aims to analyze the translations variation given for the repeated verses in the MPB and find out the reasons of the translator why they are translated similarly and sometimes different. Theories used to answer the problem in this research are the theory of Formal and Dynamic translation strategies by Nida and Taber, and the Semantic and Communicative translation strategies by Newmark, and using the theory of context and situation by Firth and Malinowski. The method used in this research is documentation (literature), with a descriptive-qualitative approach. The results of this study indicate that the translation variation is based on the structure and context of the situation contained in the Acehnese Language (BSu).